Local wisdom as stimulus for interest of young generation activators micro small and medium enterprises carved wood crafts sector - Sunariani, Ni Nyoman; Pemayun, A.A. Gde Putra (International research journal of management, IT and social sciences, 2020)
This study examines local wisdom as a stimulus for the interest of young generation activators Micro Small and Medium Enterprises carved woodcraft sector in Singakerta Village, Ubud District, Gianyar Regency. The development of Micro, Small and Medium Enterprises in Bali and Indonesia in general experienced two main obstacles, namely capital, and marketing difficulties. Capital problems hamper Micro and Small and Medium Enterprises entrepreneurs to expand their businesses and "advance class". This problem is very much related to financing access matters. The problem of this research is how local wisdom as a stimulus for the interest of young people driving the Micro and Small and Medium Enterprises in the wood carving sector in Singakerta Village, Ubud District, Gianyar. wood carving sector in Singakerta Village, Ubud District, Gianyar Regency. The current trend shows that access to financing for Micro, Small, and Medium Enterprises is predominantly based on the banking sector. The potential for financing through other sectors is still wide open with a wider access range. Financing through the non-banking sector (cooperatives, leasing, factories, pawning, capital markets), and other types of non-credit financing (grants, equity, insurance) have not been maximized by the government.